Mapping the potential of high conservation value areas at the village level in Purworejo Regency - Denni Susanto; Wiyono; Rochmad Hidayat (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2024)
High conservation value (NKT) is an assessment of outside conservation areas, including aspects of biodiversity, environmental services, and community social culture. This research aims to identify HCV potential at the village level. This research was conducted in Kedungpomahan Wetan, Kedungpomahan Kulon, and Tlogoguwo, Purworejo Regency. Structured interviews with key people in the village were conducted to obtain information about the HCVs in the village. Remote sensing approaches are also used to confirm potential HCVs. Based on the analysis results, it was found that potential HCVs were HCV 4.1, 4.2, and 5 in the three research villages, HCV 1.2 and 6 were found in Kedungpomahan Wetan and Kedungpomahan Kulon Villages, HCV 1.3 potentially existed in the three villages, and HCV 1.4 potentially existed in Tlogoguwo Village. The biodiversity aspect shows the discovery of endangered species, namely the pangolin (Manis javanica) and the slow loris (Nycticebus javanicus), which have Critically Endangered status. Aspects of environmental services are also found in the three villages, namely as flood control areas and preventing erosion. In the socio-cultural aspect, the area provides basic basic needs for the community, namely clean water and two graves. Knowing the potential of areas with high conservation value at the village level highlights the importance of management at the village level. This can be a basis for input in creating biodiversity management programs by related agencies such as the Ministry of Environment and Forestry and private agencies.